Analisa Putusan No.2400/PDT.G/2013/PA JS Tentang Pembiayaan Murabahah Dengan Wakalah - Masrudin Yusfi Albayani (Journal of Islamic Business Law, 2018)
This research aims to know analysed of chronology’s case; and analised of judgment’s judges on the verdict of No.2400/Pdt.G/2013/PA JS. The research method used juridical normatical reseach that using case, statute and conceptual approach. The law subtance are primary of law subtance, secondary of law subtance, and tertiary of law subtance. The accumulation and processing of data is the author begin whith a numbers of step. The first is determining of law subtance. The second is inventory of law subtance, and the last is analysing of law subtance. Based on analyses of the verdict mentioned above, there are two principal things that were disputed by debitor and dreditor. Debitor put in a claim that creditor acts were against the law while creditor considered that debitor broke the agreement. Those two principal things are also followed by claims for material and immaterial compensation. The judge in his verdict accepted and rejected some of the claims that were claimed by debitor and creditor.